1997
DOI: 10.3109/01902149709087370
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Secretion by Type II Pneumocytes is Inhibited by High Glucose Concentrations

Abstract: Delayed fetal lung maturation is observed in poorly controlled diabetic pregnancies. To investigate whether elevated glucose levels inhibit basal surfactant secretion and synthesis in type II cells and whether inhibitory effects on secretion can be reversed by secretagogues, type II cells isolated from 20-day fetal rat lung explants were initially cultured in [H3] choline containing media with glucose concentrations of 5.5, 10, 25, 50, and 100 mM, or in equiosmolar mannitol controls. Further incubation in nonr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Late preterm (34-37 weeks) IDMs commonly have apparent surfactant deficiency respiratory distress syndrome despite their advanced gestational age. Fetal hyperglycemia and hyperinsulinism have been associated with pulmonary immaturity and decreased synthesis and secretion by type II pneumocytes of surfactant phospholipids and their associated proteins [62][63][64][65][66]. Earlier studies indicated that high glucose and insulin concentrations inhibit the production of surfactant by blocking key enzymes in the phosphatidylcholine pathway.…”
Section: Respiratory Disordersmentioning
confidence: 99%
“…Late preterm (34-37 weeks) IDMs commonly have apparent surfactant deficiency respiratory distress syndrome despite their advanced gestational age. Fetal hyperglycemia and hyperinsulinism have been associated with pulmonary immaturity and decreased synthesis and secretion by type II pneumocytes of surfactant phospholipids and their associated proteins [62][63][64][65][66]. Earlier studies indicated that high glucose and insulin concentrations inhibit the production of surfactant by blocking key enzymes in the phosphatidylcholine pathway.…”
Section: Respiratory Disordersmentioning
confidence: 99%
“…Insulin has been reported to affect various types of ion channels and transporters in various types of cells including epithelial cells (Engle, Langan & Sanders, 1983;Kaplan et al, 1984;Marunaka, 1988;Han et al, 1996;Gewolb & O'Brien, 1997). In lung epithelia, insulin has also been reported to have effects on the amiloride-sensitive Na + -permeable channels and the bumetanide-sensitive Na + /K + /2Cl − cotransporter .…”
Section: Introductionmentioning
confidence: 95%
“…Both excessive or de cient substrate provision during fetal life can be associated with changes in fetal lung development. The infant of the poorly controlled diabetic mother has a higher incidence of respiratory distress syndrome [ 5,11] , and high insulin and glucose levels have both been found to inhibit fetal lung maturation in various experimental systems [5][6][7][8][9][10] . Maternal starvation also has been reported to result in decreased pulmonary surfactant content in fetal guinea pigs [ 26] .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that high glucose and high insulin in vitro can result in delayed fetal lung maturation [ 9,10] , a pretranslational downregulation of the fetal lung insulin receptor [ 12,13] , and decreased glucose uptake by the fetal lung [ 13] . Although downregulation of the insulin receptor might be expected to result in the maintenance of intracellular glucose homeostasis under high glucose conditions, it may be counterproductive in the short run when conditions of excess substrate are followed abruptly by substrate depletion, as may occur in infants of diabetic mothers in the immediate postnatal period or in fetuses of the diabetic pregnancy during periodic hypoglycemia in the insulin-treated mother.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation